Learning Strategies at SMK Muhammadiyah 1 Taman during the covid-19 Pandemic - Divna Diviana Risca Monica; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
The study was intended to learn online and offline learning strategies during the pandemic covid 19 at Smk Muhammadiyah 1 Taman. The study uses a descriptive, qualitative approach. The data-gathering technique used includes interviews and observations. The results of this study suggest that the covert pandemic strategy is conducted online or via other websites or media and offline or students come directly to the school as scheduled by dividing the class. If the student does not get permission, then the school will give out a long-distance learning letter. The way was because Smk Muhammadiyah 1 Taman made it compulsory for all students to attend face-to-face learning. Face-to-face learning in the season covid-19 can be implemented with: learning planning adapted to pandemic conditions; The performance of learning by placing emphasis on the transmission of materials and inlaid health protocols. Face-to-face learning is still normal despite a limited schedule of time according to government regulations.